Analisis Manajemen Kinerja Perusahaan Dalam Meningkatkan Produksi Billboard CV Kreasi Menggunakan BSC - Putri Adestiani, Icha; Abdul Jalil, Iqbal; Dewanata Putra, Pandu; Sumarno; Dwi Marselina, Resya (Jurnal Manajemen, Ekonomi, Hukum, Kewirausahaan, Kesehatan, Pendidikan dan Informatika, 2025)
This study aims to analyze the performance management of CV Kreasi during the 2022–2024 period using the Balanced Scorecard (BSC) method. BSC was chosen for its ability to provide a comprehensive view of organizational performance through four main perspectives: financial, customer, internal business processes, and learning and growth. A descriptive qualitative approach was applied, with data collected through interviews, observation, and documentation. The results indicate a significant improvement across all performance indicators, with a maximum score of 15 out of 15. Financial growth, customer loyalty, production efficiency, and employee development showed excellent performance. The implementation of BSC proved effective in aligning company strategy with operations and provided a structured framework for improving performance. This finding demonstrates that BSC can be successfully adapted by medium-sized enterprises as a strategic tool for sustainable growth.